2013
DOI: 10.1007/s12185-013-1383-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective clinical analysis of Japanese patients with peripheral T-cell lymphoma not otherwise specified: Hokkaido Hematology Study Group

Abstract: Peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) comprises a group of heterogeneous lymphomas that do not fit any other identified PTCL-subgroup and show poor prognosis. To clarify clinical aspects of Japanese PTCL-NOS patients, the Hokkaido Hematology Study Group conducted a multicenter retrospective analysis. The median age of the 107 patients (male 65.4 %) was 67 years. The majority (82.4 %) had stage III/IV disease. Following the international prognostic index, 65.7 % were categorized as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
5
2
Order By: Relevance
“…1, 4, 6, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 In contrast to our study, ∼75% of patients evaluated by the ITCLP were from Europe or Asia. Consequently, AITLs, more prevalent in Europe, and adult T-cell leukemia/lymphomas and natural killer/T cell lymphomas, which are more prevalent in Asia, were all well represented in the ITCLP series, representing ∼39% of the cases examined.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…1, 4, 6, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 In contrast to our study, ∼75% of patients evaluated by the ITCLP were from Europe or Asia. Consequently, AITLs, more prevalent in Europe, and adult T-cell leukemia/lymphomas and natural killer/T cell lymphomas, which are more prevalent in Asia, were all well represented in the ITCLP series, representing ∼39% of the cases examined.…”
Section: Discussioncontrasting
confidence: 94%
“…Therefore, a cutoff of ⩾3 was selected when the IPI was analyzed as a dichotomized variable. 4, 5, 6, 7, 8, 9 All data were analyzed using JMP 8 software (SAS, Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This may be partly because the subjects in our study were limited to patients considered able to tolerate CHOP/CHOP-like chemotherapy, and also because our study included some recently diagnosed patients. Furthermore, the CR rate (68%) of CHOP/CHOP-like therapy in our study was relatively higher than that in previous studies (39-53%) [10,[24][25]. This discordance may be also explained by several limitations including the nature of a retrospective analysis, especially various selection biases.…”
Section: Discussioncontrasting
confidence: 82%
“…In addition, our cohort shared similar clinical and biological characteristics including poor performance status, advanced stage, multiple extranodal involvement, and elevated LDH, which indicated aggressive behavior of the tumors. This could explain the low response rate to conventional chemotherapy like CHOP-based regimen and poor disease outcome of the patients with PTCL (Table 4) [3,4,[17][18][19]. Recent studies showed that peripheral blood parameters turned out to be prognostically relevant in PTCL-NOS.…”
Section: Discussionmentioning
confidence: 99%